1976
DOI: 10.3406/adh.1976.1321
|View full text |Cite
|
Sign up to set email alerts
|

La fécondité des mariages de 1670 à 1829 dans le quart nord-est de la France

Abstract: Este estudio se basa en la reconstitucion de las familias en doce pueblos escogidos por sondeo aleatorio cuya pobiacion total alcanzaba 10 583 en 1821. Debido a que cinco de dichos pueblos ne fueron escogidos al principio sino que sirvieron para reemplazar otros pueblos, hubo que ponderar los resultados. La proporcion de los nacimientos que nos fueron registrados, debido a las migraciones de las parejas y a omisiones, se puede estimar por un metodo que toma en cuenta los casamientos de los hijos de las parejas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…The summary papers of the Enquête Henry are: Henry, ‘Fécondité … sud‐ouest’; idem, ‘Fécondité … sud‐est’; Henry and Houdaille, ‘Fécondité … nord‐ouest’; Houdaille, ‘Fécondité … nord‐est’. A summary of all studies using the Henry data (before 1997) is listed in Renard, ‘Enquête Louis Henry’.…”
unclassified
“…The summary papers of the Enquête Henry are: Henry, ‘Fécondité … sud‐ouest’; idem, ‘Fécondité … sud‐est’; Henry and Houdaille, ‘Fécondité … nord‐ouest’; Houdaille, ‘Fécondité … nord‐est’. A summary of all studies using the Henry data (before 1997) is listed in Renard, ‘Enquête Louis Henry’.…”
unclassified
“…The evidence for this is largely circumstantial, unlike that in the first example, and relates to the increasing concavity of the curves for those age groups in the thirties and forties where one would expect parity-related behaviour to be most apparent (Morrow, 1978). Further examples could be drawn from the extensive literature on fertility patterns in history (see especially Wrigley, 1966Wrigley, , 1978Wrigley & Schofield, 1983;Lachiver, 1969; Osterud & Fulton, 1976; and other important French family reconstitution studies reported in Henry, 1972;Henry & Houdaille, 1973;Houdaille, 1976) and the accentuating concavity as natural fertility is abandoned appears to be a general feature. Nevertheless, the individual age-specific marital fertility rates upon which the curves are based may vary, especially amongst women in their twenties and early thirties (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…For our purposes, the ideal measure is all births per mother or all births per father: if a marriage is terminated early by the death of one party, the other has the option to remarry to attain the desired family size in the presence of controlled fertility. We would also ideally use only mothers who reached 8 The summary papers of the Enquête Henry are Henry (1972), Henry and Houdaille (1973), Houdaille (1976), and Henry (1978). A summary of all studies using the Henry data (before 1997) is listed in Renard (1997), and detailed discussion of the database can be found in Séguy and Méric (1997), , Séguy and le Sager (1999), Séguy et al (2001).…”
Section: Impq Québecmentioning
confidence: 99%